Reading Disability through Multimodal Lenses: An Appraisal and Social Semiotic Analysis of This Way, Charlie - Devan Ahmad Pramudia; Suprayogi (Universitas Islam Negeri Palopo, 2026)
This study investigates the representation of disability in the children’s picture book This Way, Charlie. While diversity in children’s literature is a growing concern, recently published books focusing on disability remain under-analyzed. Drawing on Multimodal Discourse Analysis (MDA), this qualitative study examines how verbal and visual elements co-construct the narrative of disability. The verbal data is analyzed using Martin and White’s (2005) Appraisal theory, specifically the Attitude system (affect, judgment, and appreciation), while the visual data is examined through Kress and van Leeuwen’s (2006) social semiotics. The unit of analysis includes all integrated text and illustrations from the book’s beginning to its conclusion. Findings reveal that disability is represented through various interconnected scenes, ranging from the daily life at ranch to deeper explorations of emotional insecurity and past trauma. The analysis shows that the book transcends traditional medical models of disability by framing it within the context of friendship and mutual support. This study concludes that the integration of Appraisal theory and social semiotics offers a strong framework for understanding how inclusive meanings are constructed in multimodal texts. It ultimately highlights how children’s literature can normalize diversity and foster a sense of belonging.